Genetic Diversity and Population Genetics of Mosquitoes (Diptera: Culicidae: Culex spp.) from the Sonoran Desert of North America. (3rd November 2013) - Pfeiler, Edward; Flores-López, Carlos A.; Mada-Vélez, Jesús Gerardo; Escalante-Verdugo, Juan; Markow, Therese A.
Abstract : The population genetics and phylogenetic relationships of Culex mosquitoes inhabiting the Sonoran Desert region of North America were studied using mitochondrial DNA and microsatellite molecular markers. Phylogenetic analyses of mitochondrial cytochrome c oxidase subunit I (COI) from mosquitoes collected over a wide geographic area, including the Baja California peninsula, and mainland localities in southern Arizona, USA and Sonora, Mexico, showed several well-supported partitions corresponding to Cx. quinquefasciatus, Cx. tarsalis, and two unidentified species, Culex sp. 1 and sp. 2. Culex quinquefasciatus was found at all localities and was the most abundant species collected. Culex tarsalis was collected only at Tucson, Arizona and Guaymas, Sonora. The two unidentified species of Culex were most abundant at Navojoa in southern Sonora. Haplotype and nucleotide diversities in the COI gene segment were substantially lower in Cx. quinquefasciatus compared with the other three species. Analysis of molecular variance revealed little structure among seven populations of Cx. quinquefasciatus, whereas significant structure was found between the two populations of Cx. tarsalis . Evidence for an historical population expansion beginning in the Pleistocene was found for Cx. tarsalis . Possible explanations for the large differences in genetic diversity between Cx. quinquefasciatus and the other species of Culex are presented.